Abridgment of traditional procurement and e-procurement: definitions, tools and benefits / Noraizah Abu Bakar ...[at al] - Peszynski, Konrad; Azizan, Nurdiana; Sundram, Veera Pandiyan Kaliani (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
The main aim of this paper is to contribute to our understanding of traditional procurement and electronic procurement process. Through the study of the literature, this paper concentrates on the traditional procurement and e-procurement from the perspectives of its definitions, tools and benefits. Considering the apparent shift from traditional procurement to an electronic procurement environment, public and private sector agencies worldwide can improve their procurement process, with the use of Internet-based technologies to procure goods and service. As stated by Neef (2001), if there is one sector in the economy where e-procurement can and will have an enormous effect, it is in the government. Thus, this paper makes a significant contribution to e-procurement field in rural areas development studies and research.